MODERN CONDITION AND PROSPECTS OF THE DEVELOPMENT OF ROUTE TRANSPORT OF PASSENGERS - А. Kostin; V. Savchenko-Belsky (Вестник университета)
The article analyzes the condition and prospects for the development of passenger route transport in the Russian Federation, provides the rationale for the need to improve the efficiency of public transport, which will contribute to the economic and social development of the city, region and the country as a whole. The existing problems were identified and a set of measures aimed at improving the efficiency of urban passenger transport was defined.